J. M. Coetzee’s Waiting for the Barbarians Revisited: From Apartheid to Neoliberalism - Dagamseh, Abdullah M. (SAGE open, 2022)
This article re-reads Coetzee’s Waiting for the Barbarians as a representation of Coetzee’s effort to inform the broader world of the actual terrors and crimes against humanity that existed in South Africa in the 1970s and early 1980s by extending the narrative into the later 20th and early 21st centuries. I claim that the representations in the narrative allow readers to see the novel as a critique of a global historical process that started to emerge in the late 1970s and dominate the 1980s and 1990s in South Africa and much of the rest of the world. This historical process, which has come to be called neoliberalism, is part of the larger process of colonialism. Coetzee’s novel examines various manifestations of colonialism, and it makes it clear that there is no apparent point when colonialism in South Africa, or around the world, mutated into neoliberalism. Rather, neoliberalism is an extension of the process of colonialism heading into the late 20th and early 21st centuries. To expose this continuous process of colonization, Coetzee symbolically examines colonial discourse, the contradiction inherent in the discourse of Empire, and the failure of a liberal humanist to maneuver successfully with or against the neoliberal tide.